ANALYSIS OF THE SEMANTIC STRUCTURE OF IDIOMATIC COMPOUND WORDS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
Idiomatic compound words represent a unique linguistic phenomenon where the total meaning of the unit cannot be deduced from the literal meanings of its individual components. This article provides a comprehensive analysis of the semantic structure of these units. By exploring the degrees of semantic opacity, the role of metaphors and metonymy in their formation, and the interaction between the components, the study aims to categorize idiomatic compounds based on their motivation. The research highlights that the semantic structure of such words is a result of complex cognitive processes, reflecting cultural and historical layers of language.